An introduction to equatorial electrodynamics and a review of an additional layer at low latitudes. (December 2018) - Balan, N.; Li, Qiaoling; Liu, Libo; Le, Huijun
Abstract: This paper presents a review of the progress in the understanding of an additional layer in the low latitude ionosphere, the F3 layer. A brief introduction to the daytime equatorial electrodynamics required for understanding the formation of F3 layer and formation of the usual ionospheric regions and layers are also included for continuity. Numerous papers on various aspects of F3 layer and topside ledge (F3 layer in the topside ionosphere) were published by different research groups using observations and modelling. The first time observations and important new aspects are highlighted and areas for further studies are suggested in this review. The important new aspects include an automated procedure for identifying F3 layer, global map of F3 layer and its longitudinal wave structure, solar activity variation of F3 layer and its long term trend, F3 layer in TEC, F3 layer at sunrise and sunset hours, simultaneous observations of F3 layer and upwardE xB drift velocity, simultaneous observations of F3 layer in conjugate summer and winter locations, rapid ascend of F3 layer during geomagnetic storms as an indicator of eastward prompt penetration electric field and mechanism of F4 layer. Main points are summarized at the end. Highlights: An introduction to equatorial electrodynamics and a review of F3 layer are provided. The important new aspects of F3 layer are highlighted. Suggestions for further studies of F3 layer are given.